2022
DOI: 10.3390/math10030349
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Listening on EEG Functional Connectivity of Brain: A Short-Duration and Long-Duration Study

Abstract: Music is considered a powerful brain stimulus, as listening to it can activate several brain networks. Music of different kinds and genres may have a different effect on the human brain. The goal of this study is to investigate the change in the brain’s functional connectivity (FC) when music is used as a stimulus. Secondly, the effect of listening to the subject’s favorite music is compared with listening to specifically formulated relaxing music with alpha binaural beats. Finally, the effect of the duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Music’s characteristics, such as melody, harmony, and rhythm play an important role on the listener’s emotions. However, the effect of music on the psychological aspects is more individual and differs from one person to another for the same piece of music due to its links to memories, culture, and experience which does not make for example relaxation music always effective [ 25 ]. Using self-chosen music reduces the effect of bad memories, and increases the interaction with it which helps to induce pleasure and distract the child’s attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Music’s characteristics, such as melody, harmony, and rhythm play an important role on the listener’s emotions. However, the effect of music on the psychological aspects is more individual and differs from one person to another for the same piece of music due to its links to memories, culture, and experience which does not make for example relaxation music always effective [ 25 ]. Using self-chosen music reduces the effect of bad memories, and increases the interaction with it which helps to induce pleasure and distract the child’s attention.…”
Section: Discussionmentioning
confidence: 99%
“…Music is one of the effective, non-invasive, and non-pharmacological techniques that has attracted attention for its effect in reducing dental anxiety [ 23 , 24 ]. Music induces an anxiolytic effect and improves mental skills as it can stimulate the relaxation brain’s waves such as alpha, beta, and theta, and increase the functional connection between the brain’s regions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that music can change functional connectivity [ 38 , 39 ]. Based on the analysis of functional connectivity of microstates, we found that happy music affects the characteristics of the brain functional network during the process of cognitive reappraisal.…”
Section: Discussionmentioning
confidence: 99%
“…Marimpis et al [ 19 ] reported high accuracies in the Arousal–Valence classification using functional connectivity features within the DEAP dataset [ 20 ]. Mahmood et al reported that even a short duration of listening to music can change the functional connectivity in the brain, proportional to the genre of music [ 21 ].…”
Section: Introductionmentioning
confidence: 99%